Bisphenol A-induced ultrastructural changes in the testes of common marmoset - Vijaykumar, Tushara; Singh, Dipty; Vanage, Geeta R.; Dhumal, Rohit V.; Dighe, Vikas D. (Indian journal of medical research (New Delhi, India : 1994), 2017)
Bisphenol A (BPA) is an endocrine disruptor that is widely used in the manufacture of polycarbonate plastics, epoxy resins and dental sealants. It is known to have adverse effects on spermatogenesis in rodents. This study was aimed to evaluate the effects of BPA in adult common marmoset owing to its similarities with human spermatogenesis. Sixteen marmosets were divided into four groups (n=4 per group) and given oral doses of BPA (2.5, 12.5 and 25 μg/kg BW/day) for 70 days to cover two spermatogenic cycles, and the control group received only vehicle (honey). Testes were processed for histological and transmission electron microscopy studies. Histology of the testis showed sloughing of germ cells into the lumen, increase in interstitial space and vacuolation of Sertoli cell cytoplasm. Ultrastructural analysis of the testis revealed several degenerative effects on the basement membrane, Sertoli cells, Leydig cells and other developing germ cells in the 12.5 and 25 μg/kg BW/day groups as compared to control. The observed ultrastructural changes caused by BPA in testicular morphology might be indicative of a perturbed sperm production. Considering the genetic and spermatogenic similarities of common marmoset (Callithrix jacchus) and humans, the study findings are of significance. Further studies are, however, needed to elucidate the mechanism of action.